(untitled) (CAHIERS MAGELLANES-NS, 2024)
ABTRACT : The purpose of this research work is to provide a detailed structural design of unit bay frame of an power house under different loading conditions. The study and analysis that we have carried out in this study gives a brief idea regarding the methodology in analysing , modelling and designing of powerhouse under different types of loading conditions. The critical combinations and applications of loads at required particular locations in this project has been highlighted which was found out after extensive study of the behaviour of structure for all possible loading cases using STAAD.Pro software in this study we analysed the frame structure under different loading combinations keeping in view the earthquake , floods ,wind loads etc and the results we got satisfied the applied load combinations under which the structure is safe. From the design calculations it is observed that the proposed sizes of structural elements are safe for critical load combinations. As we have carried out the study in Staad pro software, the results may vary from researcher to researcher or under different approaches depending upon the values used for different loading combinations and other factors The methods used in this design has taken into account all the possible drastic effects on the frame structure especially the forces associated with the natural calamities.